Razão de Estado e Razão Governamental: uma análise comparada entre a razão de Estado em Maquiavel e a razão de Estado como governamentalidade em Michel Foucault - Souza, Ivan Clementino de (2019)
The present thesis has as the main achievement to establish a comparative analysis between the State Ratio according to Machiavelli and the State Ratio as governmentality according to Michel Foucault. Using this comparative analysis, the goal here is to identify the reasons why Foucault does not consider Machiavelli as a State Ratio theorist, considering that all the classic politics tradition recognizes this position occupied by the philosopher. Moreover, this research seeks to verify whether it is possible to identify something new which could be originated from this comparison between these two perspectives about the State Ratio, corresponding to different representations of power, and to the same extent, deepen Foucault’s point of view, whose main concern applies to the governance behavior, in opposite to the concept originally formulated by Machiavelli. This research is justified by the relevance of Michel Foucault thought for the comprehension of the power new structures developed between the XVI and XVII centuries in the West, based on the concept of power as “the governance of behavior”. The methodology used will be hermeneutics basically, and the instruments used will be the lectures which were transformed in texts collected from Michel Foucault’s courses in the 70’s, in addition the books which were published during the same decade. Aiming the research theme comprehension, it was necessary to formulate the concept of State Ratio by Machiavelli and confront it with State Ratio as governmentality by Michel Foucault, focusing both representations of power, strategic and theoretical, analyzed by the French philosopher. The results which were obtained present that Foucault’s comprehension about this period, about this type of composition, this new power economy, brings the government as a sovereignty supplement. The State Ratio as governmentality is loaded with new elements which were not in Machiavelli’s thought yet. When Foucault announces the State Ratio as a historical governmentality form, he does not see the classic ratio, but the classic ratio loaded with new governance behavior techniques which will be intertwined with the sovereign power